2019
DOI: 10.1037/xhp0000691
|View full text |Cite
|
Sign up to set email alerts
|

Relevant for us? We-prioritization in cognitive processing.

Abstract: Humans are social by nature. We ask whether this social nature operates as a lens through which individuals process the world even in the absence of immediate interactions or explicit goals to collaborate. Is information that is potentially relevant to a group one belongs to ('We') processed with priority over information potentially relevant to a group one does not belong to ('They')? We conducted three experiments using a modified version of Sui and colleagues' (2012) shapelabel matching task. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 45 publications
2
14
1
3
Order By: Relevance
“…Similarly, the results contrast to prior work in which a significant ingroup-advantage (with a similar sample size) in the context of well-established teams was found even when the self and ingroup pairings were presented within the same task blocks 28 . The results are, however, consistent with a recent study showing minimal ingroup prioritisation was lower in magnitude than self-prioritisation when the two kinds of social stimuli were salient at the same time, and barely present when other ingroup members were not known at all 27 , as was the case in the present study. These findings suggest that novel ingroup-biases do not follow exactly the same patterns as those for established groups, particularly when competing with the saliency of the self.…”
Section: Experiments 2—competition Between Self and Ingroupsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, the results contrast to prior work in which a significant ingroup-advantage (with a similar sample size) in the context of well-established teams was found even when the self and ingroup pairings were presented within the same task blocks 28 . The results are, however, consistent with a recent study showing minimal ingroup prioritisation was lower in magnitude than self-prioritisation when the two kinds of social stimuli were salient at the same time, and barely present when other ingroup members were not known at all 27 , as was the case in the present study. These findings suggest that novel ingroup-biases do not follow exactly the same patterns as those for established groups, particularly when competing with the saliency of the self.…”
Section: Experiments 2—competition Between Self and Ingroupsupporting
confidence: 93%
“…Novel groups, however, may not hold enough weight to retain attention when task demands increase and the self competes for attention. This is supported in a recent study 27 , which found significantly reduced ingroup-prioritisation compared to self-prioritisation when groups were randomly and arbitrarily assigned with no information given about the other group members. This point highlights an important methodological consideration: if novel group-biases do not always follow the same patterns as established group-biases, then studies utilising minimal group paradigms hold the potential of showing a different pattern of responses.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This effect is extremely pervasive and consistent. For example, it has been found when stimuli represent a self-collective (Constable, Elekes, et al, 2019;Enock et al, 2018;Moradi, Sui, et al, 2015;Moradi, Yankouskaya, et al, 2015), when stimuli are avatars (Payne et al, 2017;Woźniak et al, 2018), and for space (Strachan et al, 2020). The effect has also been demonstrated in multiple languages and cultures (e.g.…”
Section: The Present Studiesmentioning
confidence: 95%
“…Hence, even without highly overlearned familiar stimuli in the self‐relevant condition, a difference in the processing of self‐relevant content and non‐self‐relevant content can still be reliably obtained (e.g. see Constable, Elekes, Sebanz, & Knoblich, 2019; Humphreys & Sui, 2016; Schäfer, Wesslein, Spence, Wentura, & Frings, 2016).…”
Section: Introductionmentioning
confidence: 99%